Analisis Efektivitas Pola Komunikasi pada Perusahaan Event Organizer PT. BeCom Solo - Wildan hafiz; Rosyihan ihza firdaus; Sentot Imam Wahjono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of organizational communication patterns at PT. Berlian Communication (BeCom) Solo, a company engaged in event organizing and marketing events. A descriptive qualitative approach was used, with data collected through in-depth interviews, observation, and documentation. The findings reveal that PT. BeCom applies two main communication patterns: the wheel pattern and the star pattern. Communication occurs bidirectionally through both formal and informal media such as meetings, WhatsApp, and email, with active employee involvement in idea development and event execution. The study also identifies internal conflicts, including compensation issues, cultural clashes, and structural tensions, which negatively affect organizational performance, particularly in terms of productivity and employee loyalty. Conflict resolution strategies include employee involvement in decision-making, cross-cultural training, and accurate human resource mapping. Overall, the communication patterns implemented at PT. BeCom play a crucial role in enhancing coordination, work effectiveness, and fostering a participatory and adaptive work environment.